2020
DOI: 10.1186/s13287-020-01991-2
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mesenchymal stem cell-derived exosomes promote plasminogen activator inhibitor 1 expression in vascular cells in the local microenvironment during rabbit osteonecrosis of the femoral head

Abstract: Background Nontraumatic osteonecrosis of the femoral head (NONFH) is a highly disabling orthopedic disease in young individuals. Plasminogen activator inhibitor 1 (PAI-1) has been reported to be positively associated with NONFH. We aimed to investigate the dysregulating PAI-1 in bone marrow mesenchymal stem cells (BMMSCs) and vascular cells in rabbit steroid-induced NONFH. Methods To verify the hypothesis that BMMSCs could promote thrombus formation in a paracrine manner, we collected exosomes from glucocort… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Inhibiting the BMPR2/Smad1/5/9 pathway inhibited osteogenesis of BMSCs, inhibited angiogenesis of HUVECs, and promoted adipogenic differentiation of BMSCs [ 61 ], which identified a new gene target for inhibiting NONFH. CD41-deficient exosomes extracted from necrotic tissue of NONFH can inhibit osteogenic differentiation and migration of MSCs; the target pathway is the ONFH-Exo-CD41-integrin β3-FAK (focal adhesion kinase)-Akt-RUNX2 pathway [ 62 ]. By searching for suppressed miRNA in patients with ONFH, scientists found that miRNA-122-5p targeting SPRY2 (rapid development growth factor homologue 2) through the RTK/Ras/MAPK pathway promoted osteoblast proliferation and differentiation in vitro and inhibited the progression of BMSCs in vivo.…”
Section: Orthopedic Disease Environmentmentioning
confidence: 99%
“…Inhibiting the BMPR2/Smad1/5/9 pathway inhibited osteogenesis of BMSCs, inhibited angiogenesis of HUVECs, and promoted adipogenic differentiation of BMSCs [ 61 ], which identified a new gene target for inhibiting NONFH. CD41-deficient exosomes extracted from necrotic tissue of NONFH can inhibit osteogenic differentiation and migration of MSCs; the target pathway is the ONFH-Exo-CD41-integrin β3-FAK (focal adhesion kinase)-Akt-RUNX2 pathway [ 62 ]. By searching for suppressed miRNA in patients with ONFH, scientists found that miRNA-122-5p targeting SPRY2 (rapid development growth factor homologue 2) through the RTK/Ras/MAPK pathway promoted osteoblast proliferation and differentiation in vitro and inhibited the progression of BMSCs in vivo.…”
Section: Orthopedic Disease Environmentmentioning
confidence: 99%
“…To investigate the mechanism of action of NONFH exosomes’ impacts on osteogenesis and angiogenesis, we conducted a miRNA sequence. Many differentially expressed miRNAs were identified in exosomes from multiple MSCs and the broad biological significance importance of exosomal miRNAs on osteogenesis and angiogenesis of NONFH has been investigated, including miR-21, miR-26a, miR-148a-3p, miR-451-5p, and miR-365a-5p [ 18 , 21 , 39 41 ]. The downstream target genes of these miRNAs include PTEN, PDCD4 PAI-1, and SAV1.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes were reported to influence osteogenic differentiation and angiogenesis to regulate bone reconstruction and homeostasis [ 14 17 ]. Recent studies have revealed that exosomes from multiple mesenchymal stem cells (MSCs) could be used for NONFH in rats [ 18 21 ]. However, no previous study has reported the effect of exosomes from necrotic bone tissues (NONFH exosomes) on the pathogenesis of NONFH.…”
Section: Introductionmentioning
confidence: 99%
“…The Agilent Bioanalyzer 2100 system (Agilent, USA) was used to quantify RNA. The library preparations were analyzed on the illumina Hiseq platform for gene clustering and sequencing as previously described [ 21 ]. The data were obtained from Novogene Bioinformatics Technology (China).…”
Section: Methodsmentioning
confidence: 99%